Role of Hemostatic System and Endothelium Activity in Development of Acute and Chronic Cerebrovascular Accidents - Alisya Morley Morley, Phoebe Candyce Lacy Bridget Lita Solmaz (Academic Journal of Clinicians, 2023)
Endothelial dysfunction plays an important role in the pathogenesis of thrombosis, neoangiogenesis, vascular remodeling, intravascular platelet activation, etc. [31,38,43], which contributes to the development of CVA. Unfortunately, the literature does not sufficiently cover the issue of laboratory determination of the functional activity of the endothelium in cerebrovascular disorders, the interaction of the endothelium and the hemostasis system in acute and chronic cerebrovascular accidents, as well as the participation of hemostatic system and endothelium activity in these processes, so we consider it extremely interesting and relevant to study indicators of endothelium dysfunction and hemostatic system in such patients to establish the role of changes in the hemostatic system and functional activity of the endothelium in the mechanisms of development of acute and chronic cerebrovascular accidents to optimize laboratory diagnostics of the severity and outcome of the disease.